Studies in constructive theology - Newlands, George M. (The University of Edinburgh, 2004)
This submission centres on substantive issues of constructive theology, and particularly on interpreting the love of God. The focus is on the multi -layered impact of a Christology of divine love, developed through five monographs (I began to look at concepts of love as key to exegesis in theology in my Ph.D. thesis, published as EXEGESIS AND METHOD IN HILARY OF POITIERS, 1978).

THEOLOGY OF THE LOVE OF GOD (1980) explores concepts of the love of God as the basic structuring element of Christian theology. In engagement with interpretations of love in the tradition, and with contemporary use of concepts of faith, hope and history, it is proposed that the nature of God as love shapes every aspect of theology. This is exemplified through analysis of the relationship between creation and redemption, understood as one dynamic movement, disrupting boundaries of redemption.

IN GOD IN CHRISTIAN PERSPECTIVE (1994) the enterprise is developed further. An understanding of God as a multifaceted model draws on Christology and Trinity, faith and practice in community. God is personal, self -differentiated being, transcendent, yet also immanent in the created order as hidden divine presence. The core elements -faith and revelation, divine action and Christology -are reappraised in the light of current theological proposals. Doctrines interact in a web of connection to shape Christian practice. A Christian understanding retains the basic core of unconditional love, Christologically characterised. A contemporary concept of God draws upon these core elements, and upon a retrieval of the historical traditions from which they arise. It can be articulated in language intelligible to contemporary citizens, and its consequences spelled out within the complexity of contemporary cultures.

Generosity and the Christian Future (1997) carries this thesis to a further stage through engagement with the emancipatory theologies, postmodernity, and political theory. The study re- imagines the framework of the divine love conceived as generosity. The need to be as alert to potential future as to past developments, and to relate doctrine to political theory and cultural issues, is grounded in theological -more precisely kenotic-Christological argument. Attention is paid to issues of human rights, violence, gender and the power structures of the churches themselves.

JOHN AND DONALD BAILLIE TRANSATLANTIC THEOLOGY (2002), built on first access to the Baillie Papers, lies at the heart of this submission. I regard the work of the Baillies as seminal to the understanding, justification and revisioning of a progressive Christian theology. This is a theological biography of the Baillie brothers. It traces in detail the interaction of their theology within the cultures in Europe and America in which they worked - notably in the circle of the `critical realists.' It sheds light on the huge influence of the Baillies in Scotland. This tradition is a trajectory against the stream today. I judge it to offer significant resources, combining conceptual plasticity with distinctive direction, for the future.

THE TRANSFORNTATIVE IMAGINATION -RETHINKING INTERCULTURAL THEOLOGY (2004). This comparative study of connections between theology and culture, through the arts, the sciences, political and human rights issues, shapes reflection on the mystery of God in a postfoundational frame. Reciprocity between ethical issues and questions of transcendence is explored. This yields a reconception of theological methodologies, in which theology, and paradoxically Christology, is seen as a catalyst rather than a trump card in interdisciplinary projects -exemplified through specific instances in the humanities, the sciences and in politics.

The central theme of the divine love is spelled out in two shorter studies in less technical style. THE CHURCH OF GOD (1984) comments critically on traditions of church, ministry and sacraments in denominational cultures, stressing the Christological imperative to be an always outward looking church. MAKING CHRISTIAN DECISIONS (1985) assesses Christian input into specific ethical issues. I include also the jointly produced collections Studies in Scottish Church History (2000), BELIEVING IN THE TEXT (2004), EXPLORATIONS IN THEOLOGY 8 (1981), and FIFTY KEY CHRISTIAN THINKERS (2004), together with a selection of published articles. The submission documents a project with a distinctive accent on the love of God as Christological leitmotif. It conceives theology as a generous approach to the transcendence of God and the consequences of incarnation.